Effect of Bacilli Calmette-Guerin vaccine on severe combined immunodeficiency patient: a narrative review and proposed workup algorithm - Joshi, Helly M.; Oza, Yugam R.; Tousif, Meirajuddin J.; Mannava, Anjali S.; Shah, Jash K.; Gondalia, Shrinath V. (International Journal of Research in Medical Sciences, 2023)
This systematic review critically investigates the administration of the Bacillus Calmette-Guérin (BCG) vaccine in neonates with severe combined immunodeficiency (SCID). The BCG vaccine, derived from Mycobacterium bovis, is a live attenuated vaccine recognized for its significant role in mitigating the impacts of tuberculosis (TB) in endemic areas. Despite its beneficial effects in controlling TB, safety and efficacy concerns have been raised when the vaccine is administered to SCID patients, who have a severe dysfunction or absence of the immune system. The potential for the vaccine to lead to severe complications due to the immunocompromised state of SCID patients necessitates a comprehensive investigation. To better understand these issues, a thorough literature review was carried out, integrating data from clinical trials and observational studies available on the PubMed database. An extensive review and analysis of 32 relevant articles revealed substantial evidence of complications from BCG vaccination in SCID patients. These findings emphasize the urgency for a more effective pre-vaccination screening process to circumvent potential adverse effects. Given the crucial role of the BCG vaccine in controlling TB, its potential to induce severe complications in SCID patients warrants careful consideration. Therefore, this review proposes an in-depth screening algorithm for newborns before BCG vaccination administration. The goal is to prevent these adverse events, offering critical insights to health policymakers, researchers, and clinicians in the field.